Holistic Recovery: Integration of Emotional, Social, and Spiritual Support Extended Family for Parentless Children at HKBP Pardamean - Tambun, Roy Haries Ifraldo (Fakultas Filsafat Universitas Advent Indonesia, 2025)
Parentless is a condition of parental absence that significantly impacts children's emotional, social, and spiritual development. Data shows 20.9% of children in Indonesia live without father presence, with 408,347 divorce cases in 2024. This study aims to describe the impact of parentless conditions and explore the role of extended family as a holistic recovery strategy for parentless children at HKBP Pardamean. A qualitative method with descriptive approach was employed through literature study and interviews with 6 parentless children. Research findings indicate that parentless conditions cause prolonged trauma, emotional regulation difficulties, excessive anxiety, social interaction problems, societal stigma, and spiritual identity crisis. Extended family proved to provide support in four dimensions: emotional-psychological, parental figure substitution, financial-material, and social status recovery. All respondents confirmed receiving comprehensive support from their extended family. Extended family plays a vital role as an effective alternative support system addressing parentless impacts. This integration model successfully helps children recover from trauma and remain connected to social-spiritual values, providing practical contributions to alternative parenting strategies within Indonesian cultural context.